(untitled) (Medico Legal Update, 2021)
By the metagenomic analysis detected the microorganisms in acne disease. The Taxonomic assignment of the sequences determined classified them into diverse microorganisms. In present study the microorganisms were bacteria (95.29%), eukaryote (4.23%), viruses (0.29%), archaea (0.04%), other sequences(0.15%) and unclassified sequences (0.00)these results determined for PA1. similarly, the PA2 was contains bacteria (96.52%), eukaryote (3.15%), viruses (0.18%), archaea (0.05%), other sequences(0.08%) and unclassified sequences (0.00). The identified and taxonomic of the bacteria that apparent high presenting 95.29% and 96.52% for each PA1and PA2 respectively. According this results taxonomic of bacteria to genus present to detected the important genus was infection acne. The PA1 sample was similarity with PA2. The genus bacteria for (PA1 and PA2) were Corynebacterium (34.67%, 40.32%), Propionibacterium (32.23%, 24.04%), Staphylococcus (24.54%, 24.18%), Malassezia (1.13%, 0.86%), Bacillus (0.92%, 1.99%), Pseudomonas (0.54%, 1.17%), Escherichia (0.36%, 0.52%), Acinetobacter (0.33%, 0.58%), unclassified (0.32%, 0.20%), Stenotrophomonas (0.31%, 0.51%), Meiothermus (0.30%, 0.36%) and Enterococcus(0.17%, 0.45%) whereas the PA2 have 0.18% of Streptococcus but the PA1 not appearance Streptococcu.